Analysis of Public Information Disclosure on the Development of Pattuku Limpoe Village in Lappariaja District, Bone Regency - Aras Solong; Tety Dwiyanti; Dzulqarnain Aras (Jurnal Syntax Transformation, 2025)
The research is motivated by the essential role of transparency in good governance, especially in village development, where public access to information ensures accountability and community participation. Despite the legal framework established by Indonesia’s Public Information Disclosure Law (UU KIP No. 14/2008), many villages, including Pattuku Limpoe, still face significant challenges in implementing effective information disclosure due to technological and resource constraints. This study aims to assess the extent of public information disclosure in village development and identify factors influencing the disclosure process in Pattuku Limpoe Village, Lappariaja District, Bone Regency. A qualitative approach was used to describe community experiences related to the implementation of village development. Data collection methods included direct observation of relevant events, interviews with key informants to gather primary data, and document analysis to review regulations and other materials related to the development process. The findings show that information disclosure in village development has not been fully achieved. The absence of an electronic system, such as a village website, limits the dissemination of information to the public. Furthermore, the lack of trained human resources in information and communication technology further hampers effective public information disclosure. These constraints highlight the need for improved technological infrastructure and capacity building among village officials to enhance transparency and accountability in village governance, in line with public policy objectives and the mandates of UU KIP No. 14/2008.